ABOUT THE SECOND LIAPOUNOV’S METHOD IN SYSTEMS WITH IMPULSIVE ACTION - Гургула, Степан Іванович; Перкатюк, Ігор Йосипович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The question of firmness of decisions of the systems of differential equalizations is explored with impulsive action in the fixed moments of time. The criteria of firmness, asymptotic firmness and instability of decisions of such systems are got.